Sustained Egr-1 Response via p38 MAP Kinase Signaling Modulates Early Immune Responses of Dendritic Cells Parasitized by Toxoplasma gondii - ten Hoeve, Arne L.; Hakimi, Mohamed-Ali; Barragan, Antonio (Frontiers in Cellular and Infection Microbiology, 2019)
As a response to a diverse array of external stimuli, early growth response protein 1 (Egr-1) plays important roles in the transcriptional regulation of inflammation and the cellular immune response. However, a number of intracellular pathogens colonize immune cells and the implication of Egr-1 in the host-pathogen interplay has remained elusive. Here, we have characterized the Egr-1 responses of primary murine and human dendritic cells (DCs) upon challenge with the obligate intracellular parasite Toxoplasma gondii. We report that live intracellular parasites induce a sustained high expression of Egr-1 in DCs, different from the immediate-early Egr-1 response to parasite lysates, inactivated parasites or LPS. Moreover, a distinct nuclear localization of elevated amounts of Egr-1 protein was detected in infected DCs, but not in by-stander DCs. The ERK1/2 MAPK signaling pathway mediated the canonical immediate-early Egr-1 response to soluble antigens in a MyD88/TLR-dependent fashion. In contrast, a non-canonical extended Egr-1 response that relied primarily on p38 MAPK signaling was induced by intracellular parasites and was exhibited similarly by MyD88-deficient and wildtype DCs. The extended phase Egr-1 response was dramatically reduced upon challenge of DCs with T. gondii parasites deficient in GRA24, a secreted p38-interacting protein. Further, Egr-1-silenced primary DCs maintained their migratory responses upon T. gondii challenge. Importantly, Egr-1 silencing led to elevated expression of co-stimulatory molecules (CD40, CD80) in Toxoplasma-infected DCs and in LPS-challenged immature DCs, indicating that Egr-1 responses suppressed maturation of DCs. Moreover, the IL-12 and IL-2 responses of Toxoplasma-challenged DCs were modulated in a GRA24-dependent fashion. Jointly, the data show that the Egr-1 responses of DCs to microbial external stimuli and intracellular stimuli can be selectively mediated by ERK1/2 or p38 MAPK signaling, and that Egr-1 can act as an intrinsic negative modulator of maturation in primary DCs.